(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The area of applied linguistics known as error analysis was created to take the place of contrastive analysis (CA).Both theories, however, explain error origins in distinct ways. Contrastive analysis only recognises errors as the product of the First Language Learner’s intervention (L1). Error Analysis (EA) acknowledges a wide variety of error causes, including, among others, intra-lingual interference, overgeneralization, and fossilization. Since there are countless possible problems, fixing them is not always easy for teachers. As a result, Corder’s reasonable reconstruction has been used to investigate the errors Fifty examples of English speaking mistakes were gathered using this theory, and numerous grammatical issues were found. in addition to misinformation, omission, intrinsic difficulty, erroneous input, and so on., thirty samples of faults in speaking English were collected, and many were discovered. To correct these errors, instructors, researchers, and institutions should take appropriate initiatives to engage and stimulate students in studying and speaking English. In this essay, we looked at a variety of issues related to speaking English at the undergraduate level in Bangladeshi universities. The article’s materials include published books, papers, and data gathered.